Decitabine prior to salvaged cord blood transplantation for acute myeloid leukaemia/myelodysplastic syndrome not in remission. (3rd October 2020) - Yao, Wen; CHU, Xiandeng; Fang, Xinchen; Zhu, Xiaoyu; Tang, Baolin; Wan, Xiang; Geng, Liangquan; Tong, Juan; Song, Kaidi; Zhang, Xuhan; Qiang, Ping; Sun, Guangyu; et al.
Abstract: What is known and objective: Many refractory/relapsed haematological malignancies, in non‐remission state, still have poor prognosis even after allogeneic haematopoietic stem cell transplantation. Recently, decitabine or umbilical cord blood transplantation (UCBT) seemed to be effective in these patients. However, few studies have added decitabine to myeloablative conditioning regimens for UCBT in patients with haematological malignancies not in remission. Therefore, the objective was to evaluate the clinical outcomes of patients with refractory/relapsed acute myeloid leukaemia (AML) or myelodysplastic syndrome (MDS) using decitabine as part of a myeloablative conditioning regimen prior to salvaged unrelated UCBT at our centre. Methods: We enrolled 20 consecutive patients with refractory/relapsed AML/MDS between 2013 and 2018. All patients were in non‐remission state before transplantation. All transplants were performed with decitabine as part of the myeloablative conditioning regimen, which was decitabine + fludarabine/busulfan/cyclophosphamide. Results and discussion: All patients achieved neutrophil and platelet engraftment. Incidence of grade III/IV acute graft‐vs‐host disease (GVHD) was 20.0%, which was also decreased compared to non‐decitabine group ( P = .025). The median follow‐up time after UCBT was 29 months (range 14‐64 months). The 2‐year probability of GVHD‐free relapse‐free survival (GRFS) was higher in the decitabine group. Univariate showed that the decitabine group was associated with a higher GRFS than the non‐decitabine group. The estimated probability of overall survival and relapse was 55% and 20.0%, respectively. What is new and conclusions: Our results suggest that addition of decitabine as part of the myeloablative conditioning regimen prior to UCBT for refractory/relapsed AML/MDS in patients who are not in remission is safe and might be an effective treatment option. Abstract : We evaluated the clinical outcomes of patients with refractory/relapsed AML or MDS using decitabine as part of a myeloablative conditioning regimen prior to salvaged unrelated UCBT at our center. The 2‐year probability of graft‐versus‐host disease‐free relapse‐free survival (GRFS) was higher in the decitabine group.